Comprehensive Analysis of Solar Photovoltaic System Defects and Inspection Techniques in Tropical Environments Using Thermal UAV: Study Case in Marang, Terengganu - Muhmad Kamarulzaman Aisyah Marliza; Wan Mohd Jaafar Wan Shafrina; Abu Bakar Nurul Asyiqin; Chew Kelvin; Khairi Anuar Nazarul Ikram; Anuar Alif Izzuddin; Mat Som Ahmad Fikrie; Mohamad Zamri Sofiah; Hafiz Zainorzuli Muhammad Zahirul (E3S Web of Conferences)
Solar power plays a key role in sustainable energy development. However, tropical climates pose challenges such as high temperatures and humidity, requiring a deep understanding of PV system defects. This study uses unmanned aerial vehicle thermographic inspection techniques to assess defects in solar farms in Marang, Terengganu, aiming to improve solar energy reliability in tropical environments. Results show that Bypass Diode issues are the most common defect, making up 75.70% of occurrences, indicating a critical area for remediation. Clusters of Thermal Anomalies (CTA) defects follow at 13.20%, necessitating detailed examination of abnormal thermal patterns. Faulty Interconnections are less frequent at 1.90%, highlighting the need for proper electrical connections. Hot spots and Overheating Component defects account for 8.70% and 0.40% respectively, pointing to localized overheating and potential malfunctions. The study also examines the correlation between solar irradiance patterns and PV defects, with irradiance levels ranging from 700.6 W/m² to 1073.1 W/m², showing how sunlight intensity fluctuations impact PV system performance. This analysis helps prioritize resources and develop targeted maintenance strategies, enhancing the reliability and performance of solar energy systems in tropical climates. The findings offer practical insights for advancing renewable energy infrastructure in tropical regions, promoting the sustainable adoption of solar energy worldwide.